Pulmonary Vascular Function in Insulin Resistance and Diabetes - Moral-Sanz, Javier; Moreno, Laura; Cogolludo, Angel; Perez-Vizcaino, Francisco (Current Vascular Pharmacology, 2014)
Insulin resistance and diabetes are current clinical concerns due to their increasing prevalence in western societies and in developing countries. Cardiovascular alterations, affecting both macro- and microcirculation, are among the major causes of illness and premature death within patients with insulin resistance or diabetes. However, the detrimental effects of insulin resistance and diabetes in the lungs are less clinically apparent, or at least masked by the progression of these metabolic diseases on other target organs. Epidemiological and experimental data suggest a link between pulmonary arterial hypertension and diabetes. Thereby, hemodynamic derangements in uncontrolled diabetes or insulin resistance are predisposing factors leading to early pulmonary alterations that in association with a second hit might accelerate the onset of pulmonary vascular disease and pulmonary hypertension. The present article reviewed the current knowledge about the effects of insulin resistance and diabetes in a territory which has received little attention until recently: the pulmonary circulation.
Keywords: pulmonary hypertension